Risk factor analysis for cytomegalovirus reactivation under prophylaxis with letermovir after allogeneic hematopoietic stem cell transplantation. Issue 6 (28th July 2022) - Mizuno, Kota; Sakurai, Masatoshi; Kato, Jun; Yamaguchi, Kentaro; Abe, Ryohei; Koda, Yuya; Kataoka, Keisuke; Mori, Takehiko
Abstract: Background: Letermovir has been approved as a novel cytomegalovirus (CMV) prophylactic agent after allogeneic hematopoietic stem cell transplantation (HSCT). However, there are still insufficient data to properly evaluate the real‐world role of letermovir, and the risk factors for CMV reactivation under letermovir prophylaxis have not been clarified. Methods: We performed a single‐institution retrospective analysis of patients under prophylaxis with or without letermovir who underwent allogeneic HSCT between March 2012 and December 2019. In August 2018, letermovir was added to the clinical practice at our institution for the prophylaxis of CMV reactivation in allogeneic HSCT recipients. Patients who underwent HSCT without prophylactic letermovir from March 2012 until September 2018 served as a historical control. Results: The cumulative incidence of clinically significant CMV infection (CS‐CMVi) was significantly lower in the letermovir group than in the historical control group not receiving letermovir (30.2% vs. 71.6%, p < .05, at 100 days). In addition, the cumulative incidence of non‐relapse mortality (NRM) at day 500 was significantly lower in the letermovir group (4.7% vs. 19.8%, p < .05). We then performed a risk factor analysis for developing CS‐CMVi in the letermovir group. The only significant factor identified by this multivariable analysis was transplantation from a CMV seronegative donor to a seropositive recipient (Hazard ratio = 2.76, 95% confidence interval 1.14–6.68, p < .05). Conclusion: Our study showed that letermovir prophylaxis significantly reduced the incidence of CS‐CMVi and NRM in a real‐world setting and that the CMV serostatus of the donor remained as a risk factor for CS‐CMVi even under letermovir prophylaxis.